FAKTOR-FAKTOR YANG MEMPENGARUHI KESUKSESAN SISTEM INFORMASI KEUANGAN DAERAH BERBASIS AKRUAL DI KABUPATEN ACEH BESAR - Ikhyanuddin Ikhyanuddin (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2017)
This study aims to look at the success rate of financial management informationsystem. The research variables consisted of information quality, system quality,service quality, user satisfaction, usage and net benefits. The population of thisstudy consists of all government unit of Banda Aceh and Aceh Besar district. Therespondents are users SIPKD namely officials financial manager, treasurer and treasurer reception. Sample selected by survey methods, which the entire population used as the research sample. Methods of data analysis using Structural Equation Modeling (SEM) with Lisrel 8.8 tools. The results using De Lone and McLean IS SuccessModel (2003) showed that out of 9 hypotheses constructed, 7 hypotheses show theeffect. Two other hypotheses do not show the influence that the quality system is touse and the quality of service to use. Overall SIPKD can be considered a success.